An Intelligent Per-decision Method of State Grid Accidents in Big Data Environments. Issue 2 (June 2019) - Li, Dianyang; Tan, Chen; Wang, Hongzhe; Han, Da; Qin, Ling; Zhang, GuangCheng; Lou, Tianyue; Xiu, Tian
Abstract: Aiming at the problem of hard to per-alarm the state grid accidents in big data environment, this paper proposes an intelligent per-decision method of state grid accidents. This method divides the management of state grid data into two parts, i.e. analysis of state grid data and intelligent expert database. The part of analysis of state grid data consists of input layer, facility layer and accident layer. Establish the self-learning intelligent expert database by means of connecting weight values of input and output nodes and threshold values of output nodes. Compare with the per-data that comes from the part of analysis of state grid data and the data from intelligent expert database, then achieve the goal of per-decision of state grid accidents and dispatch the accidents. A case and simulation results show that this method is implementable. In addition, this method provides beneficial thinking to solve the state grid accidents per-alarm in big data environment.